[PP.09.05] THE POLISH REGISTRY FOR FIBROMUSCULAR DYSPLASIA (ARCADIA-POL STUDY) – DISTRIBUTION OF VASCULAR BED INVOLVEMENT AND COMPLICATIONS IN PATIENTS WITH FIBROMUSCULAR DYSPLASIA. (September 2017) - Warchol-Celinska, E.; Hanus, K.; Florczak, E.; Prejbisz, A.; Januszewicz, M.; Michalowska, I.; Swiatlowski, L.; Talarowska, P.; Janaszek-Sitkowska, H.; Stryczynski, L.; Protasiewicz, M.; Niemirska, A.; et al.
Abstract : Objective: To assess the vascular bed involvement and vascular complications in patients with fibromuscular dysplasia (FMD) enrolled into ARCADIA-POL study. Design and method: Out of 182 patients enrolled into ARCADIA-POL study since January 2015 (instituted on the basis of Polish-French collaboration) we present 144 patients with confirmed FMD in at least one vascular bed. A standardized FMD data form was used for data collection. All patients underwent detailed clinical evaluation including ABPM, biochemical evaluation, biobanking, duplex Doppler of carotid and abdominal arteries and whole body angio-CT. Results: In our analysis we included 144 patients with confirmed FMD (112F[77.8%], 32M[22.2%], mean age:41.1 ± 16.3 years. 132 patients (91.7%) were hypertensives. The mean age at the diagnosis of hypertension was 33.9 ± 15.4 years and the FMD was diagnosed 6.8 ± 10.6 years later with the mean age at the diagnosis of FMD of 40.7 ± 16.3 years. In the analyzed group FMD was identified in renal arteries in 127 (88.2%) patient as well as in carotid, intracranial and vertebral arteries in 24(16.7%), 20(13.9%) and 9(6.3%) patients, respectively. FMD was also identified in celiac trunk and mesenteric, iliac and splenic arteries in 19(13.2%), 11(7.6%), and 15(10.4%) patients, respectively. In 56 patients (38.9%) FMD was identified in two or more vascular beds. Two vascular beds were involved in 23.6%(34 pts), three in 9%(13 pts), four in 3.5%(5 pts), five in 2.1%(3 pts) and six in 0.7%(1 pt). Arterial dissection(s) or aneurysms in various vascular beds were found in 10.4% and 33.3% of patients respectively. Aortic abnormalities coexisting with FMD lesions were found in 3 patients(2.1%). Severe FMD - defined as first onset of FMD <30 years, affecting at least 3 vascular beds complicated with thrombosis or dissection requiring an endovascular or surgical repair, with no inflammatory background - was identified in 5 patients (3.5%). Conclusions: The data of ARCADIA-POL registry showed that renal FMD was the most frequent, but also cerebrovascular FMD was found in relatively large proportion of patients. Our data revealed high incidence of FMD lesions coexisting in different vascular beds as well as relatively frequent occurrence of vascular complications.